Women's perceptions of successful financial retirement planning - Durrheim, Meghan (Rhodes University, Faculty of Commerce, Department of Management, 2018)
Financial retirement planning is an important component in ensuring that individuals accumulate sufficient wealth for retirement. Previous research suggests that many individuals are unable to accumulate sufficient wealth for retirement with the problem being particularly acute for women as they tend to spend less time planning financially for retirement when compared to men. Consequently, many women are unable to accumulate sufficient wealth for retirement. Despite the growing need to investigate women's financial retirement planning, much research tends to focus on financial retirement planning for males. Consequently, there is a growing need to investigate women's perceptions of successful financial retirement planning, particularly in Grahamstown. After conducting an in-depth literature study and using the study done by Doa (2014), six independent variables were identified: values, time horizon, attitudes, working life-cycle, risk tolerance and financial literacy. These independent variables were identified as factors which could potentially influence women's perceptions of successful financial retirement planning. A set of hypothesis were formulated to test the relationship between these independent variables and the dependent variable (women's perceptions of successful financial retirement planning). The study comprised of 101 participants. A principle component analysis was performed to determine the key variables, with the relevant independent factors being renamed: cultural values, personal values, affective attitudes, time horizon knowledge, time horizon consideration, risk tolerance, financial literacy. An ordinal logit regression analysis was then conducted on these renamed variables to determine the influence of these key independent variables on the dependent variable. After controlling for a set of demographic variables the results of the ordinal logit regression analysis revealed that only affective attitudes, time horizon knowledge, and personal values had a significant relationship with women's perceptions of successful financial retirement planning. Cronbach's alpha revealed that the measuring instrument of the significant extracted factors was reliable, while Pearson product moment was used to determine correlations between extracted key independent variables and the dependent variable. The investigation into women's perceptions of successful financial retirement planning enabled insightful information to be gathered which adds to the body of knowledge. In addition, recommendations were formulated in an attempt to assist women when making financial retirement decisions.
Keywords: Women -- Retirement -- South Africa -- Makhanda; Retirement -- Planning; Retirement income -- Planning; Women -- Finance, Personal; Retired women -- Finance, Personal; Regression analysis